Warming Effects on Periphyton Community and Abundance in Different Seasons Are Influenced by Nutrient State and Plant Type: A Shallow Lake Mesocosm Study - Hao, Beibei; Wu, Haoping; Zhen, Wei; Jo, Hyunbin; Cai, Yanpeng; Jeppesen, Erik; Li, Wei (Frontiers in Plant Science, 2020)
Periphyton plays an important role in lake ecosystems processes, especially at low and intermediate nutrient levels where periphyton contribution to primary production can be similar to or exceed that of phytoplankton. Knowledge of how periphyton responds to key drivers such as climate change and nutrient enrichment is, therefore, crucial. We conducted a series of mesocosm experiments over four seasons to elucidate the responses of periphyton communities to nutrient (low and high, TN-0.33 mg L-l TP-7.1 µg L-1 and TN-2.40 mg L-l TP-165 µg L-1, respectively), temperature (ambient, IPCC A2 scenario and A2+50%) and plant type (two submerged macrophytes with different morphological structural complexity: Potamogeton crispus and Elodea canadensis, and their corresponding plastic imitations with similar size and structure). We found a noticeable seasonality in the abundance and composition of periphyton. In spring and summer, periphyton abundances were significantly higher in the turbid-high-nutrient state than in the clear-low-nutrient state, and in summer they were notably higher at ambient temperature than in climate scenario A2 and A2+50%. In contrast, periphyton abundances in autumn and winter were not influenced by nutrient and temperature, but they were notably higher on plants with a more complex morphological structure than simple ones. The genus composition of periphyton was significantly affected by nutrient-temperature interactions in all seasons and by plant type in winter. Moreover, periphyton functional composition exhibited noticeable seasonal change and responded strongly to nutrient enrichment and temperature rise in spring, summer and autumn. Our results suggest that the effect of warming on periphyton abundance and composition in the different seasons varied with nutrient state and host plant type in these mesocosms, and similar results may likely be found under field conditions.